Symbiont-Mediated Insecticide Detoxification as an Emerging Problem in Insect Pests - Blanton, Alison G.; Peterson, Brittany F. (Frontiers in Microbiology, 2020)
Pesticide use is prevalent with applications from the backyard gardener to large-scale agriculture and combatting pests in homes and industrial settings. More than $14 billion are spent annually in the US and, globally, the pesticide budget is estimated at almost $60 billion. Along with this demand, the selective pressure generated by sustained pesticide use has become a concern leading to environmental contamination, pest resistance, and, thus, reduced pesticide efficacy. Despite efforts to improve the environmental impact and reduce off-target effects, chemical pesticides are relied on and control failures are costly. Though pesticide resistance mechanisms vary, one pattern that has recently emerged is symbiont-mediated detoxification within insect pests. The localization within the insect host, the identity of the symbiotic partner, and the stability of the associations across different systems vary. The diversity of insects and ecological settings link to this phenomenon and broad. In this mini-review, we summarize the recent trend of insecticide detoxification modulated by symbiotic associations between bacteria and insects, as well as highlight the implications for pesticide development, pest management strategies, and pesticide bioremediation.